2002
DOI: 10.1302/0301-620x.84b5.12679
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic failure of the Elite Plus total hip replacement, with a Hylamer acetabulum and Zirconia ceramic femoral head

Abstract: We report catastrophic early failure of a cemented total hip replacement comprising a modular femoral component with a Zirconia ceramic head and an acetabular component of cross-linked ultra-high molecular-weight polyethylene (Hylamer). Between 1995 and 1999 we implanted 29 hips in 26 patients with a mean age of 49.2 years. Survivorship analysis in this group revealed a failure rate of 67.6% at five years. All hips which failed did so because of aseptic loosening with progressive osteolysis or radiolucencies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 24 publications
1
32
0
1
Order By: Relevance
“…Another possibility is that revision rates of zirconia-polyethylene THAs were disastrous and surgeons simply stopped using a device without studying the differences. However, disastrous clinical results, even if in an unexpected direction, tend to be submitted and accepted, as in the cases of early zirconia heads [1,10] or Hylamer TM [24]. Therefore, unpublished studies that would have shifted the meta-analysis toward better clinical results for zirconia are unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that revision rates of zirconia-polyethylene THAs were disastrous and surgeons simply stopped using a device without studying the differences. However, disastrous clinical results, even if in an unexpected direction, tend to be submitted and accepted, as in the cases of early zirconia heads [1,10] or Hylamer TM [24]. Therefore, unpublished studies that would have shifted the meta-analysis toward better clinical results for zirconia are unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded irrelevant studies if the title and abstract indicated obviously irrelevant topics, such as dental materials, knee arthroplasty, and basic research including animal experiments, biomaterials, and simulators. We excluded dual publication, uncontrolled studies, studies without the number of revised cases, clinical studies that covered only enhanced UHMWPE (Hylamer TM ), which produced disastrous clinical results compared with UHMWPE [24], or if they only discussed ceramic-onceramic THA (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there is sometimes poor correlation between laboratory wear studies and wear measured in vivo. Hylamer (DePuy DuPont Orthopaedics, Wilmington, DE, USA), for example, was shown to have low in vitro wear but exhibited catastrophic wear and failure in vivo [16,33]. Additionally, although the wear volume in HXLPE has been shown to be less in vitro than conventional UHMWPE [18,19], some studies have suggested that it generates smaller particulate debris [10] that are more biologically active in stimulating osteolysis in vitro [31], whereas recent evidence suggests fewer small particles are generated with HXLPE [4].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the ability to translate positive findings from hip simulator studies to equally good results clinically has proven challenging [29,32,39]. This highlights the importance of confirming the safety and wear performance of new materials in clinical studies using a sensitive evaluation technique.…”
Section: Introductionmentioning
confidence: 99%